Lullaby & Labor: Alice Notley and the Work of Poetry. (13th November 2018) - Turner, Lindsay
Abstract: The poetic form of the lullaby represents, at its origin, the simultaneous presence of poetic production and gendered domestic or reproductive labor. As is the case with many other forms of lyric, however, the lullaby's work-related origins are often obscured. This gesture means the expulsion of the laboring (usually maternal) body from the realm of poetry. In this essay, through the early work of the contemporary American poet Alice Notley (Songs for the Unborn Second Baby [1979], and Waltzing Matilda [1981] ), I read closely into the forms of song and lullaby. Although Notley's work is frequently examined in terms of its feminist contribution to epic genre, attention to these lyric forms lets us see both types of labor in sharper focus, fleshing out (literally) a context of physical and emotional work. At the same time, through Notley's poetry, poetic work comes to provide a nuanced and flexible model for conceptualizing gendered reproductive labor – a task that, especially given the conditions of the feminization and globalization of work at present, is as urgent as it is daunting.